Implementation of the 1996 amended zoning ordinance of Dumoy area in Davao City - Almonte, Rosindo J.
This study, entitled "Implementation of 1996 Amended Zoning Ordinance of Dumoy Area in Davao City' was undertaken to determine the extent of implementation of the 1996 Amended Zoning Ordinance particularly in protected area of the four barangays, namely: Bago Aplaya, Bago Gallera, Dumoy and Baliok known as the Dumoy area, taken from the famous name of Dumoy Water, the source of water supply of the City of Davao. The objectives of the study include the determination of the extent of development in this area in terms of land use changes from 1994 (before the issuance of the ordinance) to 2008 (while the zoning ordinance is being implemented). The study also looked into the considerations affecting the implementation of the zoning ordinance and the developments that occurred in the area. The study use the Comprehensive Land Use Plan (CLUP) map or zoning ordinance map and actual 2008 land use map to determine land use changes over the years. The reasons of conformance and non-conformance as cited by the key informants and the implementers of the zoning ordinance served as the basis for the considerations affecting the extent of the implementation and the extent of the development. In determining the extent of the development, the 1994 and the 2008 land use maps were used. With the information gathered, different land uses were computed individually for the four (4) barangays. Patterns and trends were noted, particularly before and during the implementation of the zoning ordinance. Results of the study show conversions of the vacant land to its best uses are manifested by the increases of other land uses and decreasing of vacant lands. This information postulates that development in the area is actively changing the landscape from its former agricultural land use to urban uses. Land use patterns of each barangay showed different stages of development, Despite the existence of the land use zoning ordinance, subdivision developments continue to be introduced not conforming to the required land use classifications. The dominant actual land use in the Dumoy area is residential but the zoning ordinance only allowed for Low and Medium Density Residential land uses, being a protected zone. In the present zoning ordinance, there is no industrial zone but the actual land use comprises of some light industries present in the area. It should be emphasized that most of these establishments have been there even before the enactment of the zoning ordinance. Light industries particularly related to agriculture are only allowed in the adjacent barangays of Lizada, Sirawan up to the boundary of the province of Davao del Sur at barangay Binugao. Most of the commercial establishments are located along the Davao-Cotabato National Highway. The study concluded that non-conforming land uses continue to grow and the level of development in the area also continue to contribute to future urbanization of the protected area. The researcher recommends the enhancement and capability building of the implementers of the zoning ordinance for them to be able to implement and instill the tenets of land use regulatory power of the Local Government Unit(LGU) to protect its natural resources, the underground water source as mandated by the Local Government Code. The LGU should take action to protect the source of water by institutionalizing the mobile septage cleaning of individual household septic tank for proper waste disposal. It is also recommended that strict regulation, if not prohibition, of the proliferation of gasoline stations along national highway should be enforced.